1828 La. Acts 367-368 - (:unkn) unknown (My University, 1828)
25: If any person shall challenge another, or shall accept a challenge to fight with sword, pistol, rapier or other dangerous weapon, every person so challenging or accepting such challenge, shall, upon conviction thereof, be fined not exceeding five hundred dollars, and may be imprisoned not exceeding two years
Keywords: DUELING